2019
DOI: 10.1002/met.1783
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of meteorological droughts across South Australia

Abstract: An understanding of drought characteristics is vital for sustainable management of water resources. This is particularly important for dry regions such as Australia where large‐scale water supply infrastructure has to be designed to withstand multiyear variability in rainfall anomalies. This study considers the Standardized Precipitation Index (SPI) at time scales of 3, 6, 12 and 24 months to assess both short‐term and long‐term droughts. Trends in the SPI at 46 selected rainfall stations across South Australi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…At present, most of the research studies hydrological and meteorological drought using copula function, and seldom combine the research results with crop data [44,45]. The annual drought disaster in China leads to severe grain production, so it is urgent to further study regional agricultural drought [46].…”
Section: Discussionmentioning
confidence: 99%
“…At present, most of the research studies hydrological and meteorological drought using copula function, and seldom combine the research results with crop data [44,45]. The annual drought disaster in China leads to severe grain production, so it is urgent to further study regional agricultural drought [46].…”
Section: Discussionmentioning
confidence: 99%
“…Rainfall station density is estimated as number of selected stations (45 in our case) divided by the study area (1,028,790 km 2 ). Some other studies used similar data point density as follows: rainfall stations density was used by Bari Abarghouei et al (2011) as '0.25' in Iran, Li et al (2011) as '0.28' in China, Zhang et al (2015 as '0.48' in China, Akinsanola andOgunjobi (2017) as '0.25' in Nigeria, andRashid andBeecham (2019) as '0.47' in South Australia per 10.000 km 2 .…”
Section: Study Area and Datamentioning
confidence: 99%
“…They stated that south-eastern Australia experienced an exceptional drought in this period, particularly New South Wales, Victoria, and Queensland with insufficient rainfall, decreased soil moisture, and increased temperature and evapotranspiration. In another study, Rashid and Beecham (2019) focused drought characterization of meteorological drought in South Australia by using monthly rainfall data of 46 rainfall stations (during the period 1960-2010) at 3-, 6-, 12-, and 24-month durations SPI, and they found that 23 of 46 rainfall stations had a negative trend for longterm drought (24-month SPI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought will potentially cause drastic consequences for global water resources management [1] agriculture production [2], ecological protection [3], as well as economic and social development [4]. Detecting and understanding the characteristics of the previous droughts are the preconditions to predict drought and of great importance for water resource management [5].…”
Section: Introductionmentioning
confidence: 99%